Impact of perioperative blood transfusion on survival in pancreatic neuroendocrine tumor patients: analysis from the US Neuroendocrine Study Group. Issue 7 (July 2020) - Marincola Smith, Paula; Baechle, Jordan; Solórzano, Carmen C.; Tan, Marcus; Lopez-Aguiar, Alexandra G.; Dillhoff, Mary; Beal, Eliza; Poultsides, George; Cannon, John G.D.; Rocha, Flavio G.; Crown, Angelena; Cho, Clifford; et al.
Abstract: Background: Packed red blood cell (PRBC) transfusion has been associated with worse survival in multiple malignancies but its impact on pancreatic neuroendocrine tumors (PNETs) is unknown. The aim of this study was to determine the impact of PRBC transfusion on survival following PNET resection. Methods: A retrospective cohort study of PNET patients was performed using the US Neuroendocrine Tumor Study Group database. Demographic and clinical factors were compared. Kaplan–Meier and log-rank analyses were performed. Factors associated with transfusion, overall (OS), recurrence-free (RFS) and progression-free survival (PFS) were assessed by logistic regression. Results: Of 1129 patients with surgically resected PNETs, 156 (13.8%) received perioperative PRBC transfusion. Transfused patients had higher ASA Class, lower preoperative hemoglobin, larger tumors, more nodal involvement, and increased major complications (all p < 0.010). Transfused patients had worse median OS (116 vs 150 months, p < 0.001), worse RFS (83 vs 128 months, p < 0.01) in curatively resected (n = 1047), and worse PFS (11 vs 24 months, p = 0.110) in non-curatively resected (n = 82) patients. On multivariable analysis, transfusion was associated with worse OS (HR 1.80, p = 0.011) when controlling for TNM stage, tumor grade, final resection status, and pre-operative anemia. Conclusion: PRBC transfusion is associated with worse survival for patients undergoing PNET resection.